GENETIC RESOURCES OF RICE (ORYZA SATIVA L.) WITH COLORED PERICARP - O. V. Zelenskaya; G. L. Zelensky; N. V. Ostapenko; I. G. Tumanyan (Вавиловский журнал генетики и селекции, 2018)
The rice plant (Oryza sativa L.) provides nutrition for more than half the world’s population. Traditionally it is considered an Asian crop, but it is also cultivated in Africa, America, Australia and Southern Europe. The main areas of rice growing in the world are occupied with the white-grained varieties. Wild-growing ancestors of cultural rice had a colored grain pericarp. In the countries of traditional rice growing, along with white-grained varieties, red and black grain rice varieties are grown as a dietary and therapeutic product. It is used for food without preliminary grinding of the grains, therefore all nutrients and biologically active substances this culture is valued for are preserved. Rice with the colored grain pericarp has a higher antioxidant activity than white-grained. The review presents data on the content of antioxidant compounds in the varieties of the red- and black-grained rice: phenolic acids, lavonoids, γ-oryzanol, anthocyanins, proanthocyanidins, etc. Aiming at these useful properties of rice plants with a colored grain pericarp, the leading rice-growing countries work on breeding of the modern pigmented rice varieties. In European countries, Italy and France, the red and black grain varieties of rice with a high content of phytochemical elements have also been bred based on Asian varieties. Breeding of rice varieties with colored grain pericarp was started in the Russian Federation in 2001. As a result, the following rice varieties were developed: red-grained Mars and Rubin (2012), as well as the black-grained glutinous variety Yuzhnaya Noch (2014), which are included in the RF State Register of Protected Breeding Achievements. These varieties have been revealed to contain a large amount of oleic and linolenic acids (up to 43 % each), whereas only their traces are found in the white-grained rice variety Rapan. There are signiicant diferences in the content of antioxidants: Rapan has 7 mg/100 g; Mars and Rubin, 45 mg/100 g; Yuzhnaya Noch, 105 mg/100 g. These varieties have been introduced into commercial production and are used for dietary nutrition and as a starting material for the creation of new exclusive varieties of rice.